Antes não, agora sim! protagonismo juvenil, projeto de vida e processos de ressingularização na escola: um olhar a partir do Programa Ensino Integral em São Paulo - Carli, Flávio Dalera de (2018)
Not then, right now is about processes of rediscovering singularities on the students and educators’ comprehension of the world that emplaces educational cultures in specific contexts. Two Sao Paulo’s public state high schools of the Fulltime Teaching Program (PEI), named schools A and B, were studied with the goal of understanding the transforming power of a pedagogic project that puts the centrality on the student as a determinant condition for the school’s modus operandi, built upon the encouraging of its’s protagonist the student, and considering the making of a life project significantly protagonistic. The project also works to comprehend what eases both individual and collective learning paths takes students to a new existential plateaus, to an right now that did not exist before. The empirical data from school A were collected between 2012 and 2015 with the teaching Program’s professional attendance, whereas school B’s were collected in 2017, with the hearing of 3 groups of students and interviews with school professionals. The analysis of the data resulted in the construction of a descriptive an analytical text, coherent to the Gilles Deleuze and Felix Guattari constructionism, which is the base of the whole work, and inspired by the prose analysis proposed by Marli Andre. On the researched contexts the students were able to find meaning on the scholar activities, presenting motivation for the success of a vitally ethical project, and the educators assure that they have reencountered a reason to be in their professions for so they can see the result of their labour. It is considered that is the “between” of the relations between students and teachers, when based in humanistic pedagogical ideals for the promotion of the self preservation, the preservation of the others and the preservation of time that keeps lit the flame for a emancipating transformation. Youth Protagonism and life projects are concepts developed based on Antonio Carlos Gomes da Costa and Willian Damon. Experiential learning such as the condition of transformation and reflexive thought are considered under the definition of Claude Dubar and put alongside Gisele Toassa’s concept of experience. The relation power/knowledge is taken from Tomas Tadeu Silva and from Bernard Charlot’s considerations about the subject. The concept of scholar failure has its roots on Maria Helena de Souza Patto. The student protagonism at school is understood as the promoter of the empirical knowledge so that the experience of the protagonism and of the life project may contrast the singularities of the relations with power, looking forward to the construction of a self-centered life project which promotes the necessity of the appropriation of the knowledge. The school is what the subjects make of it when appropriating its contexts in their circumstances. Autonomy and emancipation are concepts based upon Paulo Freire. The tutors in these movements are taught upon Vera Maria Nigro de Souza Placco and Vera Lucia Trevisan de Souza’s theories. Having said that, this thesis dare to announce: Evoé, youngsters at sight!